The Pragmatic Court: Reinterpreting the Supreme People’s Court of China - Zhang, Taisu (Columbia Journal of Asian Law, 2012)
This Article examines the institutional motivations that underlie several major developments in the Supreme People’s Court of China’s recent policy-making. Since 2007, the SPC has sent off a collection of policy signals that escapes sweeping ideological labeling: it has publically embraced a populist view of legal reform by encouraging the use of mediation in dispute resolution and popular participation in judicial policy-making, while continuing to advocate legal professionalization as a long-term policy objective. It has also eagerly attempted to enhance its own institutional competence by promoting judicial efficiency, simplifying key areas of civil law, and expanding its control over lower court adjudication. This Article argues that the strongest institutional motivation underlying this complex pattern of activity is, contrary to some common assumptions, neither simple obedience to the Party leadership nor internalized belief in some legal reform ideology, whether legal professionalism or populism. Instead, it is the pragmatic strengthening of the SPC’s own financial security and sociopolitical status-the SPC is, in many ways, a “rational actor” that pursues its institutional self-interest. This theory of “institutional pragmatism” brings unique analytical cohesion to the SPC’s recent behavior, giving us a clearer sense of its current priorities and, perhaps, its future outlook.